1986
DOI: 10.1001/archderm.1986.01660230045008
|View full text |Cite
|
Sign up to set email alerts
|

Normocholesterolemic Xanthomatosis

Abstract: Hypercholesterolemia deadly culprit in the cause of coronary vascular disease, but is it always, or even commonly, the cause of atherosclerosis? The answer is clearly not always, as other factors also play a role in the complex problem of how lipids accumulate in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 3 publications
0
40
0
1
Order By: Relevance
“…Although, elevation in the mean cholesterol or low-density lipoprotein cholesterol (LDL-C) levels has been reported, XP can also be seen in patients with normal lipid levels 8 9. In the latter group, reduced high-density lipoprotein cholesterol (HDL-C), altered lipoprotein content or structure have been implicated 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…Although, elevation in the mean cholesterol or low-density lipoprotein cholesterol (LDL-C) levels has been reported, XP can also be seen in patients with normal lipid levels 8 9. In the latter group, reduced high-density lipoprotein cholesterol (HDL-C), altered lipoprotein content or structure have been implicated 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthomas can also occur in normolipemic patients, although rarely, with the exception of lipid deposits limited to the palpebral area, the so-called xanthelasma. 1 Xanthoma lesions have been described with or without hyperlipidemia in association with monoclonal immunoglobulin (MIg). Cremer et al 2 first reported on this association in 1937.…”
Section: Introductionmentioning
confidence: 99%
“…Increased amounts of plant sterols, particularly sitosterol, stigmasterol, campesterol, and their 5-alpha derivatives are deposited on the arterial walls and in xanthomas in patients with sitosterolemia 21) . The unusually high content of plant sterols in the circulatory lipoproteins has been postulated to possibly promote the deposition of these sterols in the arterial walls [22][23][24][25] . Thus, treatment to reduce serum plant sterol levels in patients with sitosterolemia is crucial for preventing life-threatening cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%